Nature and Characteristics of Wildlife Tourism in the Kgalagadi Transfrontier Park: Array - Tichaawa, Tembi; Lekgau, Refiloe Julia (Acta Universitatis Danubius. Œconomica, 2020)
Southern Africa is a prominent wildlife destination in the continent. The sub-continent houses a wide range of protected areas, including national parks, game reserves and Transfrontier parks. The overall purpose of the present study was to explore the nature and characteristics of wildlife tourism in the Kgalagadi Transfrontier Park and adjacent communities. The study adopted a qualitative approach and included two case study areas in South Africa and Botswana. In total, 26 interviews were purposively collected from tourism stakeholders within the two communities. Key findings show the Kgalagadi Transfrontier Park to be a low impact Park with visitor restrictions. Additionally, the nature of wildlife tourism differed in the two communities, in which one largely focused on the integration of culture and tradition in the tourism experiences while the other was limited to being a transit site. The study recognised culture and conservation values as the two prominent wildlife tourism characteristics in the host communities of the Kgalagadi Transfrontier Park, which thereby places restrictions to the scale of tourism development in the region but offering tourism diversification opportunities for the adjacent communities